Avaliação dos efeitos de fármaco anti-hipertensivo nas alterações hepáticas associadas à esquistossomose murina - Teixeira, Danúbia Pinheiro (2019)
Schistosomiasis is a systemic disease, caused by the Schistosoma sp. Trematode and its advanced form is morphologically represented by the presence of periportal liver fibrosis. Treatment of schistosomiasis is limited and Praziquantel (PZQ) is the drug used in this process. The objective of the study was to evaluate, in vivo, the effect of an antihypertensive, hydrazine (HDZ), isolated or associated with PZQ, on the development of murine infection by Schistosoma mansoni, evaluating the effects on hepatic tissue in the formation, evolution and development microstructure of granulomas; Formation of fibrosis in addition to vascular alterations. In parallel, the formation of granulomas in other organs, such as spleen and lung, was also evaluated. The total number of granulomas showed that the SM infection control group and the HDZ treated and infected group had a significantly higher number when compared to those receiving praziquantel treatment (p <0.001). There was also a predominance of productive exudative granulomas in all infected animals regardless of treatment. However, there was a greater number of organized granulomas in the infected animals that received HDZ when compared to the other groups (p <0.05). The results related to the density of collagen fibers, the area, volume and mean diameter of the granulomas showed an immunomodulation process in the evolution of the granulomas of the infected animals that received the HDZ, since they presented a higher percentage of collagen (p <0.001) compared to the other groups. In addition, a greater value of the total number of vessels in the hepatic tissue of the infected animals treated with HDZ was observed in relation to other groups. In a way that HDZ did not interfere in the schistosomicidal action of PZQ nor in the migration of eggs to other organs such as spleen and lung. HDZ appears to play a significant role in the healing process by inducing increased collagen formation in acute schistosomal granulomas. It is necessary to develop further studies about the induction of HDZ in the formation of collagen, not only in the acute phase, but also in the chronic one.